Wpływ formy własności na efektywność banków komercyjnych - Rosiek, Janusz; Zyguła, Andrzej (The Impact of the Ownership Forms on the Commercial Banks' Efficiency, 2009)
The increase of the efficiency is one of the most indicated reasons of the banks' consolidations. The purpose of the article is an answer to the question: "Did the consolidation that takes place in Polish commercial banks' section have an impact on their efficiency?". In respect of the majority of the conditionalities, which describe the banks' effectiveness, the number of the factors has been limited. The authors focused in their research on one of them, namely on the form of ownership. To examine the impact of the form of ownership on the commercial bank's efficiency, the ANOVA method has been used, and as a measure of the effectiveness the effectiveness ratios have been applied. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 825-834